Reaksi Pasar Sektor Properti dan Real Estat atas Penjualan Perdana Mega Proyek Meikarta - Pitriani, Ni Ketut Modi; Wirama, Dewa Gede (E-Jurnal Akuntansi, 2020)
The launching of Meikarta mega project gained positive response from customers. As many as 17,435 apartment units was sold on the day the project was launched. Because of its huge scale, the Meikarta has the potential to boost the property and real estate sector that was down at the time. The aim of this research is to analyze the information content of Meikarta project, especially for firms in the property and real estate sector. The information content is to be identified by market response, which in turn to be measured by abnormal return using market-adjusted model with five-day event windows around the launching date. Sample consists of 48 firms in the property and real estate sector. The results of the analysis show that there is no statistically significant market response to the launching of Meikarta project. Therefore, it is concluded that the Meikarta project does not have any information content. Keywords: Meikarta; Property and Real Estate Sector; Information Content; Market Reaction; Abnormal Return.